Growth of exclusively breastfed small for gestational age term infants in the first six months of life: a prospective cohort study - Nurani, Neti; Wibowo, Tunjung; Susilowati, Rina; Hastuti, Janatin; Julia, Madarina; Van Weissenbruch, Mirjam M. (BioMed Central Ltd, 2022)
Background: Compared to their appropriate-for-gestational-age (AGA) peers, small-for-gestational-age (SGA) infants are prone to growth deficits. As the first 6 months of exclusive breastfeeding is generally recommended, it is essential to understand how this intervention might impact SGA infants’ growth. This study aims to assess growth of exclusively breastfed SGA term infants in the first 6 months of life. Methods: A prospective cohort study was conducted on term infants born in Dr. Sardjito General Hospital and two private hospitals in Yogyakarta, Indonesia. SGA was defined as birth weight less than the 10th percentile according to Fenton criteria. Weight, length, and head circumference (HC) were measured at birth and monthly until 6 months old. Results: A total of 39 AGA and 17 SGA term infants who were exclusively breastfed in their first 6 months were included and followed. In SGA compared to AGA, birth weight, length, and HC (mean ± SD) were significantly lower (p < 0.001). During the first 6 months, the SGAs grew in weight and length in parallel with the AGAs. At sixth months of age, the weight and length (mean ± SD) of the SGAs were significantly lower compared to the AGAs (p < 0.001). However, HC (mean ± SD) of SGAs grew significantly faster than the AGAs (p < 0.005). At sixth months of age, there were no significant differences in HC between the two groups (p = 0.824). Conclusions: In the first 6 months, exclusively breastfed SGA term infants, in contrast to weight and length, only show catch up growth in HC, leading to HC comparable to their AGA peers at the age of 6 months.